Sources of Subseasonal‐To‐Seasonal Predictability of Atmospheric Rivers and Precipitation in the Western United States. Issue 6 (22nd March 2021) - Huang, Huanping; Patricola, Christina M.; Bercos‐Hickey, Emily; Zhou, Yang; Rhoades, Alan; Risser, Mark D.; Collins, William D.
Abstract: Atmospheric rivers (ARs) account for a large portion of winter precipitation in the western US. To evaluate the sources of AR and precipitation predictability at subseasonal‐to‐seasonal timescales, we examine the relationships between two climate modes, the El Niño/Southern Oscillation (ENSO) and Madden‐Julian oscillation (MJO), and winter hydroclimate in the western US. Our analysis uses a large ensemble of the Weather Research and Forecast (WRF) model simulations from 1981 to 2017, facilitating the assessment of uncertainty in climate mode‐AR relationship due to climate variability and short length of observations. Over the North Pacific basin, we find ENSO‐related latitudinal shifts of ARs, but ENSO has little effect on basin‐wide averaged AR frequency. Over the western US, there is some uncertainty in the ENSO‐AR connection due to the impacts of ENSO indices and datasets. However, extreme El Niño events defined by the ENSO longitude index are consistently linked to increased landfalling AR activity. The MJO can lead to significantly enhanced or suppressed landfalling AR activity in the large‐ensembles, depending on the phase of MJO and time lag, while observations are too short in length to robustly show this signal. ENSO substantially modulates the MJO‐AR relationship, triggering variegated responses of landfalling ARs and AR precipitation in La Niña and El Niño years. Our findings highlight the need to evaluate concurrent effects of different climate modes on ARs and precipitation, and may shed light on a path toward more accurate subseasonal‐to‐seasonal prediction of ARs and precipitation over the western US. Key Points: The El Niño/Southern Oscillation (ENSO)‐atmospheric river (AR) relationship depends on ENSO index, with enhanced landfalling AR activity during extreme El Niño Madden‐Julian oscillation (MJO) leads to significant landfalling AR and precipitation anomalies in large‐ensembles, but observations are too short to show this signal ENSO modulates the MJO‐AR relationship, thus consideration of concurrent climate modes could improve seasonal hydroclimate prediction